Trends of Medicare Reimbursement Rates for Common Plastic Surgery Procedures. Issue 5 (7th April 2021) - Siotos, Charalampos; Cheah, Michael A.; Damoulakis, George; Kelly, Jonathan; Siotou, Kalliopi; Schechter, Loren S.; Shenaq, Deana S.; Derman, Gordon H.; Dorafshar, Amir H.
Abstract : Background: Knowledge of Medicare reimbursement is essential for plastic surgeons providing care to Medicare beneficiaries. The authors sought to evaluate changes in Medicare reimbursement for common plastic surgery procedures from 2010 to 2020. Methods: The authors assessed the Physician Fee Schedule of the Centers for Medicare and Medicaid Services website. Rates of work-, facility-, or malpractice-related relative value units and total monetary units for 26 common plastic surgery procedures between 2010 and 2020 were evaluated. Descriptive statistics were used to calculate relative differences and to compare observed changes over time with the rate of inflation. Results: For the selected procedures, the authors found an average relative difference in terms of monetary units of an increase by 2.02 percent. However, after adjusting for inflation, the average relative difference was a decrease by 14.31 percent. The authors' analysis indicates that, on average, there was a 1.55 percent decrease in physician relative value units between 2010 and 2020. Conclusions: Medicare reimbursement rates have changed significantly over the past decade. However, these changes did not keep pace with the rate of inflation. Plastic surgeons should be aware of these trends and advocate for more fair reimbursement rates.